2004
DOI: 10.1097/01.mlr.0000128003.81622.ef
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of States’ Scholarship, Loan Repayment, and Related Programs for Physicians

Abstract: States' support-for-service programs bring physicians to needy communities where a strong majority work happily and with at-risk patient populations; half stay over 8 years. Loan repayment and direct financial incentive programs demonstrate the broadest successes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(107 citation statements)
references
References 13 publications
(12 reference statements)
1
101
0
Order By: Relevance
“…In addition, several states have programs aimed at retaining homegrown physicians through scholarships and grants. 22 Some have tried efforts to discourage physicians from establishing practices in oversubscribed markets. The single-payer system in Ontario, Canada, conducted a trial of reduced reimbursements to new physicians in the saturated market of Toronto.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, several states have programs aimed at retaining homegrown physicians through scholarships and grants. 22 Some have tried efforts to discourage physicians from establishing practices in oversubscribed markets. The single-payer system in Ontario, Canada, conducted a trial of reduced reimbursements to new physicians in the saturated market of Toronto.…”
Section: Resultsmentioning
confidence: 99%
“…15,16 In contrast, a study of 69 US state-run programs reported that physicians who were obligated (by return-of-service commitments) to practice in rural or underserviced areas were slightly more likely than non-obligated physicians to stay longer (55% of obligated physicians stayed over 8 years compared with 52% of non-obligated physicians). 17 This study reported that programs that provided incentives to physicians entering practice and to residents were more successful than for programs aimed at medical students. The increasing costs of medical education and student debt may decrease physicians' interest in rural practice, leading them to chose a more lucrative urban specialty.…”
Section: Personal Factorsmentioning
confidence: 94%
“…Programs, like the state-level initiatives studied, continue to be an important source of financial support for those willing to make service commitments in underserved areas. Furthermore, previous research indicates these programs are not only successful at attracting students to primary care, but that state obligated physicians are more satisfied and remain longer in their practice than non-obligated physicians [11] [30] [31]. Health care advocates and policy makers must not overlook the state role in providing loan and scholarship opportunities to meet their unique and growing needs to expand access to quality health care.…”
Section: Discussionmentioning
confidence: 99%